1999
DOI: 10.1164/ajrccm.159.4.9808008
|View full text |Cite
|
Sign up to set email alerts
|

Can Intensive Support Improve Continuous Positive Airway Pressure Use in Patients with the Sleep Apnea/Hypopnea Syndrome?

Abstract: Continuous positive airway pressure (CPAP) therapy is widely prescribed for patients with the sleep apnea/hypopnea syndrome (SAHS), but the use of CPAP for such patients is disappointingly low. We postulated that providing intensive educational programs and nursing support to SAHS patients might improve CPAP use and outcomes. We also examined the hypothesis that CPAP use would be greater among patients who had initiated their own referral than among those asked to seek help by a partner. We randomized 80 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
233
2
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(255 citation statements)
references
References 22 publications
13
233
2
7
Order By: Relevance
“…A study by ENGLEMAN et al [19] reported a low (4.30.6 h) CPAP run-time in users without reported therapy related problems and an even lower one (2.80.6 h) in those complaining of side-effects. Additionally, a recent study reported daily CPAP use (3.90.4) at similar levels to the data produced in this study for patients who received standard support for nCPAP therapy [20]. Compliance with CPAP therapy was related to the amount of OSA activity, the severity of daytime sleepiness, as well as the diagnostic follow-up procedure used.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A study by ENGLEMAN et al [19] reported a low (4.30.6 h) CPAP run-time in users without reported therapy related problems and an even lower one (2.80.6 h) in those complaining of side-effects. Additionally, a recent study reported daily CPAP use (3.90.4) at similar levels to the data produced in this study for patients who received standard support for nCPAP therapy [20]. Compliance with CPAP therapy was related to the amount of OSA activity, the severity of daytime sleepiness, as well as the diagnostic follow-up procedure used.…”
Section: Discussionsupporting
confidence: 75%
“…In patients with sleep laboratory follow-up at 9 months, residual RDI with CPAP applied was almost identical in acceptors and non-acceptors, 1 (24) Rejected CPAP immediately after CPAP titration (27) With CPAP effectiveness data (20) With missing data (4) Accepting CPAP therapy with 9 month follow-up (acceptors (74))…”
Section: Resultsmentioning
confidence: 99%
“…A recently published study demonstrated that the relief of sleepiness and other OSAS-related clinical symptoms and improvement in perceived health status was much greater in patients receiving conservative and CPAP treatment compared with those only receiving conservative treatment, even after 3 months of treatment [17]. Another study in 80 consecutive patients showed that CPAP use over 6 months was greater among patients receiving intensive than among those receiving standard support, with greater improvements in OSAS symptoms, mood, and reaction time in the intensively supported group [27]. Furthermore, a retrospective French study demonstrated that patients who continued CPAP treatment for >6 months had a relatively good perception of their health.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23] Improvements in nCPAP technology, in particular the introduction of automatic adjustments of the nCPAP pressure throughout the night (auto-CPAP), [24][25][26][27][28][29] and other attempts to enhance acceptance and compliance (positive reinforcement, psychological/educational interventions, heated humidiWcation) have been introduced. [30][31][32][33][34] We were interested to see if these actions have led to better acceptance, adherence and long-term compliance as compared to earlier reported data. We acquired data on (long-term) compliance and therapy failure.…”
Section: Introductionmentioning
confidence: 99%